Business Model Analysis of PT. Radio Suara Gontor FM (Suargo FM) as a Boarding School-Based Radio in the Era of Convergence - Tubagus, Novalul Barokah (Universitas Darussalam Gontor, 2024)
The rapid development of business models began when numerous studies examined the business environment, which was subsequently supported by advancements in digital communication and information technology. Digital transformation has changed the business landscape for companies worldwide, raising discussions about how technology influences business architecture in various fields such as strategy, business models, organizational management, processes, solutions, technology, and competencies. PT. Radio Suara Gontor FM (Suargo FM) is a radio station owned by Darussalam Gontor Boarding School, located within the Gontor Campus 1, in Gontor, Mlarak, Ponorogo. The aim of this study is to understand the business model implemented by Suargo FM as a pesantren-based radio station owned by Darussalam Gontor. Boarding School. This research uses a qualitative descriptive method. Data collection was conducted through observation, interviews, and documentation. Data analysis was performed using field data analysis techniques consisting of data reduction, data presentation, and conclusion drawing. The results of this study indicate that Suargo FM, as a Boarding School-based radio station, is unlike most other Boarding School-owned radio stations, which are community radios with a business model focused on providing broadcasting services for specific communities with a primary goal not centered on profit. Since its inception, Suargo FM has operated as a business radio station with a wide broadcast coverage area aimed at proselytizing and education while also generating profit. However, Suargo FM is not entirely profit-oriented (money oriented) because the teaching and educational approach of Pondok Modern Darussalam Gontor does not view material wealth as the output of education. In the era of media convergence, Suargo FM has transformed into digital radio as a form of adaptation to the development of information and communication technology. Keywords: Buseiness Model; Media Convergence; Boarding School-Based Radio; Suargo FM